Global real-world experiences with pembrolizumab in advanced urothelial carcinoma after platinum-based chemotherapy: the ARON-2 study - Massari, Francesco; Santoni, Matteo; Takeshita, Hideki; Okada, Yohei; Tapia, Jose Carlos; Basso, Umberto; Maruzzo, Marco; Scagliarini, Sarah; Büttner, Thomas; Fornarini, Giuseppe; Myint, Zin W; Galli, Luca; et al. (Cancer immunology, immunotherapy, 2024)
BACKGROUND: Immune checkpoint inhibitors have changed previous treatment paradigm of advanced urothelial carcinoma (UC). The ARON-2 study (NCT05290038) aimed to assess the real-world effectiveness of pembrolizumab in patients recurred or progressed after platinum-based chemotherapy. PATIENTS AND METHODS: Medical records of patients with documented metastatic UC treated by pembrolizumab as second-line therapy were retrospectively collected from 88 institutions in 23 countries. Patients were assessed for overall survival (OS), progression-free survival (PFS) and overall response rate (ORR). Cox proportional hazards models were adopted to explore the presence of prognostic factors. RESULTS: In total, 836 patients were included: 544 patients (65%) received pembrolizumab after progression to first-line platinum-based chemotherapy in the metastatic setting (cohort A) and 292 (35%) after recurring within < 12 months since the completion of adjuvant or neoadjuvant chemotherapy (cohort B). The median follow-up time was 15.3 months. The median OS and the ORR were 10.5 months and 31% in the overall study population, 9.1 months and 29% in cohort A and 14.6 months and 37% in cohort B. At multivariate analysis, ECOG-PS ≥ 2, bone metastases, liver metastases and pembrolizumab setting (cohort A vs B) proved to be significantly associated with worst OS and PFS. Stratified by the presence of 0, 1-2 or 3-4 prognostic factors, the median OS was 29.4, 12.5 and 4.1 months (p < 0.001), while the median PFS was 12.2, 6.4 and 2.8 months, respectively (p < 0.001). CONCLUSIONS: Our study confirms that pembrolizumab is effective in the advanced UC real-world context, showing outcome differences between patients recurred or progressed after platinum-based chemotherapy.
Keywords: Humans; Adjuvants, Immunologic; Pembrolizumab; karcinom z přechodných buněk; Platinum; adjuvancia imunologická; Survival; lidé; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; ARON-2 study; nádory močového měchýře; Retrospective Studies; Tumor response; Carcinoma, Transitional Cell; retrospektivní studie; platina; Urinary Bladder Neoplasms; Real-world data; Urothelial cancer